A STUDY ON THE ABILITY OF SECOND YEAR STUDENTS OF SMPN 1 KERINCI KANAN IN COMPREHENDING RECOUNT TEXT - Nur Soleha; Dahnilsyah Dahnilsyah; Marzuki Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was aimed at finding out the ability of the second year students of SMPN 1 Kerinci Kanan in comprehending recount texts. The population of this study was the second year students in academic year 2018/2019. The sample size was 30 students out of the population chosen by using cluster random sampling. The data were collected by administering a reading test of recount texts. The collected datawere analyzed and calculated by using Microsoft Excel. The findings of the research showed that the mean score of the test was 57.2 (mediocre level). Meanwhile, the mean score in terms of finding factual information is 65.3 (good level). The mean score in terms of finding main idea, meaning of difficult word, reference and restatement is 58,57.3, 56.6 and 48.6 (mediocre level). Therefore,it could be concluded that the ability ofstudents in comprehending recount texts was categorized into mediocre level.Key Words: Ability, Reading Comprehension, Recount Texts.